Learning ecology: YouTubing and content creation - Shereen Kularajasingam, *; Lee, Sze Lin * (Sunway College Kuala Lumpur, 2015)
YouTube is a popular website that hosts a huge collection of online videos which are used increasingly in and out of the classrooms by instructors and learners alike.. However, even though it is a free website, not many young people are involved in digital content creation. The authors will conduct a literature review and a case study to explore whether content creation leads to deep learning. It is hypothesised that deep learning does take place when learners are engaged in content creation.